Applying ED-XRF and LA-ICP-MS to geochemically characterize chert. The case of the Central-Eastern Pre-Pyrenean lacustrine cherts and their presence in the Magdalenian of NE Iberia. (June 2017) - Sánchez de la Torre, Marta; Le Bourdonnec, François-Xavier; Gratuze, Bernard; Domingo, Rafael; García-Simón, Luis Miguel; Montes, Lourdes; Mazo, Carlos; Utrilla, Pilar
Abstract: The geochemical characterization of several lacustrine chert formations outcropping in the Central-Eastern Pre-Pyrenean area is presented. Four geological formations were considered: one Upper Cretaceous (Tremp formation), two Oligocene (Castelltallat and Tartareu-Alberola formations) and one Miocene (Aragonian limestones formation). Furthermore, lacustrine cherts appearing in the Magdalenian levels of Forcas I and Cova Alonsé (Huesca, Spain) were also considered. Analyses were done using energy-dispersive X-ray fluorescence (ED-XRF) and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Results show different geochemical features between formations, in some cases also between outcrops, concerning major, minor and trace elements. Archaeological samples from Cova Alonsé and Forcas I fit in some of the established groups, being the dispersion area slightly different between sites. Consequently, results determine the presence of diversified lithic procurement strategies.